RBM14 enhances transcriptional activity of p23 regulating CXCL1 expression to induce lung cancer metastasis - Wen Zhang; Yulin Peng; Meirong Zhou; Lei Qian; Yilin Che; Junlin Chen; Wenhao Zhang; Chengjian He; Minghang Qi; Xiaohong Shu; Manman Tian; Xiangge Tian; et al. (Acta Pharmaceutica Sinica B)
Metastasis serves as an indicator of malignancy and is a biological characteristic of carcinomas. Epithelial–mesenchymal transition (EMT) plays a key role in the promotion of tumor invasion and metastasis and in the enhancement of tumor cell aggressiveness. Prostaglandin E synthase 3 (p23) is a cochaperone for heat shock protein 90 (HSP90). Our previous study showed that p23 is an HSP90-independent transcription factor in cancer-associated inflammation. The effect and mechanism of action of p23 on lung cancer metastasis are tested in this study. By utilizing cell models in vitro and mouse tail vein metastasis models in vivo, the results provide solid evidence that p23 is critical for promoting lung cancer metastases by regulating downstream CXCL1 expression. Rather than acting independently, p23 forms a complex with RNA-binding motif protein 14 (RBM14) to facilitate EMT progression in lung cancer. Therefore, our study provides evidence for the potential role of the RBM14–p23–CXCL1–EMT axis in the metastasis of lung cancer.